Analisa Kebijakan Sektor Lingkungan : Permasalahan Implementasi Kebijakan Pengelolaan Kawasan Hutan di Indonesia - Roby Firman syah, M.A (Journal of Governance, 2017)
Society-based on forest growth will increase the inter-society communication activities which deliver a community forum. The participation which directed to policy practice only has its weakness, that’s the inability to grow “belongingness” about forest growth program among communities. By participating actively in community forum, the conflict thoughts will be modified into empowering people in order to help government program.